Inovasi Pengolahan Cabai Merah Keriting Menjadi Chili Oil Sebagai Upaya Peningkatan Kesejahteraan Petani di Desa Tanjung Seteko - Mika Lestari; Qayla Sa’adatu Gina; Salsa Dzakia Fitriani; Endah Ayu Atika; Nur Nadya Anggraeni; Aziza Dwita Sari; Amelia Nur Zahrina; Muhammad Jordhi Dirgantarawan; M. Huanza; Nurilla Elysa Putri (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This study aims to improve the welfare of curly red chili farmers in Tanjung Seteko Village through the innovation of processing fresh chili into chili oil. The background of this research lies in the low added value of fresh chili and frequent price fluctuations that cause unstable farmer incomes. The study employed a descriptive qualitative approach involving preparation, implementation, and evaluation stages, with purposive sampling covering farmers, farmer group members, housewives, and village officials. Data were collected through observation, interviews, documentation, and questionnaires. The results indicate that processing chili into chili oil can extend shelf life up to 1–2 months at room temperature and more than 6 months under refrigeration, reduce harvest losses by 30–40%, and significantly increase economic value compared to selling fresh chili. A single production process using 5 kg of curly red chili yields 16 liters of chili oil with an estimated selling price of IDR 1.500.000-2.000.000 per production cycle, showing that simple processing activities can provide substantial added value for farmers. Beyond economic benefits, this innovation strengthens community empowerment by improving processing skills, encouraging economic independence, promoting participation in value-added businesses, and reinforcing local economic resilience. The social impacts also include youth and women empowerment and broader opportunities for local product–based entrepreneurship. The study recommends continuous capacity development, digital marketing strategies, and ongoing mentoring to optimize farmer welfare. Therefore, processing curly red chili into chili oil is a strategic solution to enhance income, skills, and sustainable rural economic development.